Kepuasan Kerja pada Karyawan Ditinjau Berdasarkan Faktor Demografik dan Motif Berprestasi - Rostiana D. Nurjayadi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2005)
This research tries to find out the relationship among achievement motivation, demographics factors and job satisfaction. The participants are 55 administration employees of one private university in west Jakarta. Data collection were held during + 2 months and to be analyzed by using Pearson Product Moment correlation. Result indicated there are significant correlations between achievement motivation and job satisfaction ( r = + 0,312, p < 0,05 ), between age and job satisfaction ( r =  - 0,315, p < 0,05 ), between work time and job satisfaction ( r = - 0,459, p < 0,05 ). The relationship findings between demographics factors and job satisfaction did not support the previous research that found positive correlations between age, work time and job satisfaction.    Key words: Job satisfaction, achievement motivation and  demographic factors